Mediterranean diet for breast cancer prevention and treatment in postmenopausal women - Potentas, Elżbieta; Witkowska, Anna Maria; Zujko, Małgorzata Elżbieta (Menopause Review/Przegląd Menopauzalny, 2015)
Breast cancer has become a big oncological concern both in Poland and most countries around the world. Epidemiological studies show that women who are directly in danger of suffering from breast cancer are mainly postmenopausal women. Due to the seriousness of the problem more attention is devoted to preventative measures that should be undertaken. That is why, Mediterranean diet and its beneficial effects on health started to be discussed. This diet contains antioxidants and shows anti-inflammatory properties which are crucial in breast cancer prevention. Its components are fish, olive oil, unrefined cereals, herbs, fruits and vegetables. In 1960s there was research done on the influence of low fat diet, as a preventative measure, on coronary artery disease. In 1980s, an interest in this diet grew and there was a great come-back to the origins of the diet. It led to estimation of its influence on cardiological and cancer diseases. Many positive effects were observed among people living in the Mediterranean area as far as health qualities of the diet are concerned. Mediterranean diet was compared with high fat diet of people living in Northern Europe and the USA. It seems to create new dietary recommendations as a preventative measure in breast cancer disease. The following article presents most recent data on the importance of Mediterranean diet as a prevention against breast cancer.